Structure-activity relationship investigation of benzamide and picolinamide derivatives containing dimethylamine side chain as acetylcholinesterase inhibitors - Xiao-hui Gao; Lin-bo Liu; Hao-ran Liu; Jing-jing Tang; Lu Kang; Hongnian Wu; Peiwu Cui; Jianye Yan (Taylor & Francis Group, 2018)
A series of benzamide and picolinamide derivatives containing dimethylamine side chain (4a-4c and 7a-7i) were synthesised and evaluated for acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibitory activity in vitro. Structure-activity relationship investigation revealed that the substituted position of dimethylamine side chain markedly influenced the inhibitory activity and selectivity against AChE and BChE. In addition, it seemed that the bioactivity of picolinamide amide derivatives was stronger than that of benzamide derivatives. Among them, compound 7a revealed the most potent AChE inhibitory activity (IC50: 2.49 ± 0.19 μM) and the highest selectivity against AChE over BChE (Ratio: 99.40). Enzyme kinetic study indicated that compound 7a show a mixed-type inhibition against AChE. The molecular docking study revealed that this compound can bind with both the catalytic site and the peripheral site of AChE.